Risk Management Model of English Program Private Schools in Bangkok - Saenrat, Siriporn; Poovatanakul, Vipaporn; Nirunthawee, Sakchai; Meekun, Kosol (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The study aims to 1. study the causal factors of risk management of private schools in Bangkok that offer English program instruction following the curriculum of the Ministry of Education; 2. theoretically develop and assess the risk management model of the private schools and 3. develop and assess the appropriateness of the risk management model of the private schools. The study was conducted in the academic year 2020 with 59 schools which was the total population of the study. The research tool was a summated rating scales questionnaire with 65 questions. Data were analyzed using frequency, percentage, mean, standard deviation, Total and Stepwise Multiple Regression Analysis (MRA), and Path Analysis with the Model fit. The results found that: 1. there were five causal factors affecting the risk management of the private schools in Bangkok that offer English program instruction following the curriculum of the Ministry of Education. The five factors included 1. law and regulation; 2. policies of the agency; 3. public communication and persuasion; 4. policies and strategies and 5. economic changes. These five factors together could predict the risk management possibility at 60.8 percent; 2. the results of the theoretical analysis of the risk management model, found that the model had correlation test values correlated with the empirical data at 76 percent, which all passed the criteria, and 3. the results of the assessment of the risk model found that the model was appropriate to be implemented in the private schools by passing the evaluation criteria from the experts which were 70/75.